2003
DOI: 10.1016/s0020-7292(03)00311-4
|View full text |Cite
|
Sign up to set email alerts
|

Labor augmentation in an Egyptian teaching hospital

Abstract: Labor augmentation and monitoring deviated from evidence-based guidelines. Obstacles to implementing protocols need to be explored.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 13 publications
2
28
0
Order By: Relevance
“…This paper presents selected findings from four studies documenting routine obstetric practices in Egypt, Lebanon, Syria and the West Bank and compares these to evidence‐based best practice. Other findings are presented elsewhere 16–20 …”
Section: Introductionmentioning
confidence: 66%
See 1 more Smart Citation
“…This paper presents selected findings from four studies documenting routine obstetric practices in Egypt, Lebanon, Syria and the West Bank and compares these to evidence‐based best practice. Other findings are presented elsewhere 16–20 …”
Section: Introductionmentioning
confidence: 66%
“…The studies in the four countries were not conducted during the same time period 16–20 . The first, in Lebanon, completed data collection in 1997 and the last, conducted in the West Bank, was completed in 2003.…”
Section: Methodsmentioning
confidence: 99%
“…This paper specifically examines the extent to which third-stage management matched practices shown to prevent postpartum hemorrhage. Other study findings are reported elsewhere [10,11]. The facility studied offers private and public care; recipients are representative of Egyptian women presenting for delivery.…”
Section: Introductionmentioning
confidence: 91%
“…An observational study in an Egyptian hospital showed that 91% of labour was augmented and that 93% of such women received inappropriate augmentation, that too without adequate monitoring [17]. …”
Section: Introductionmentioning
confidence: 99%